High Sensitivity C-Reactive Protein Level and Ischemic Heart Disease - Himayat Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To know the relation between serum hs CRP levels and IHD. Methods: This study was done in the Department of cardiology Hayatabad Medical Complex, Peshawar after approval from the hospital ethical committee. It was a cross-sectional descriptive study. The duration of the study was one and a half years, with a sample of 160 IHD patients.The sample size was calculated based on a universally validated calculator with a 95% confidence interval and a 5% margin of error. Results: Among the total 160 IHD patients included in this study, 102(63.7%) were male and 58(36.3%) females. Mean±SD age was 57.8±13.7. Among 160 patients, 32(20%) patients were having hs CRP below 1 mg/L, 45(28.1%) patients having between 1 to 3mg/L, and 83(51.9%) patients >3 mg/L. Mean±SD hs CRP level was 4.52±3.2mg/L. Conclusion: High sensitivity C-reactive proteins (hs CRP) is one of the important risk factors of IHD and its level is directly related to the frequency of IHD